การพัฒนากลไกการกำหนดนโยบายของพรรคการเมืองไทย - ปุณยวุฒิปรีดา, ภูริวัจน์ (วารสารศรีล้านช้างปริทรรศน์; Vol 7 No 2: วารสารศรีล้านช้างปริทรรศน์ ปีที่ 7 ฉบับที่ 2 (กรกฏาคม - ธันวาคม 2564), 2021)
บทความวิจัยนี้มีวัตถุประสงค์เพื่อ (1) ศึกษาวิเคราะห์สภาพทั่วไปและปัญหาอุปสรรคเกี่ยวกับการกำหนดนโยบายของพรรคการเมืองไทย (2) ศึกษากลไกการกำหนดนโยบายของพรรคการเมืองไทย (3) นำเสนอการพัฒนากลไกการกำหนดนโยบายของพรรคการเมืองไทย เป็นการวิจัยเชิงคุณภาพ ผู้ให้ข้อมูลสำคัญจำนวน 25 รูปหรือคน และการสนทนากลุ่มเฉพาะจำนวน 11 รูปหรือคน และวิเคราะห์ข้อมูลโดยใช้เทคนิควิเคราะห์เนื้อหาเชิงพรรณนา             ผลการวิจัยพบว่า 1) สภาพทั่วไปและปัญหาอุปสรรคเกี่ยวกับการกำหนดนโยบายของพรรคการเมืองไทยมีเหตุปัจจัยที่มีความซับซ้อน และหลากหลายกระจายตัวมากขึ้น โดยเฉพาะต่อเหตุผลที่อิงอยู่กับขบวนการทางสังคม การเมืองภายนอก มากกว่าอิงอยู่กับผู้นำและแกนนำภายในพรรค 2) กลไกการกำหนดนโยบายของพรรคการเมืองไทยนั้นพรรคการเมืองต้องมีความจริงใจต่อการแก้ไขปัญหาอย่างจริงจัง 3) การพัฒนากลไกการกำหนดนโยบายของพรรคการเมืองไทยโดยการนำหลักอิทธิบาท 4 มาใช้เป็นแนวทางในการกำหนดนโยบาย องค์ความรู้ที่ได้จากการวิจัยนั้นชี้ให้เห็นว่าสาระสำคัญของการพัฒนากลไกการกำหนดนโยบายของพรรคการเมืองไทยนั้น เริ่มจากการก่อรูปนโยบายจากอุดมการณ์พรรคการเมือง นำไปสู่กระบวนการในการกำหนดนโยบายทางการเมืองภายใต้กรอบที่กำหนดไว้ในรัฐธรรมนูญ ต่อมาเป็นการตัดสินใจนโยบาย แนวคิดและแนวทางการทำงานกับนโยบายของพรรค สอดคล้องและเป็นไปเพื่อประโยชน์ของประเทศชาติและประชาชน ยึดมั่นในระบอบประชาธิปไตยอันมีพระมหากษัตริย์ทรงเป็นประมุข   Abstract                     The objectives of the research were 1) to study and analyze the general conditions and obstructive problems related to policy-making mechanism of Thai political parties, 2) to study the policy-making mechanism of Thai political parties, and 3) to present the development of policy-making mechanisms of Thai political parties. It was a qualitative research, of which data were collected from 25 key informants and an eleven-person focus group discussion. The data were analyzed through the descriptive content analysis.                  The research findings were as follows: 1) The general conditions and obstructed problems, related to the policy-making mechanism of Thai political parties, were caused by more complex factors, diversified and distributed. They were specially based on external factors such as social movements and politics rather than internal factors like leaders and core persons within the parties. 2) The policy-making mechanism was based upon sincerity of Thai political parties in solving problems seriously. 3) The development of policy-making mechanism of Thai political parties was engaged in the political parties’ policy making, based upon the Buddhist principle of Iddhipāda. The knowledge base from the research demonstrated that the essence of development of Thai political parties’ policy-making mechanism began with the policy formation from their political ideologies leading to the process of political policy formation within the framework stipulated in the constitution. Later, a policy decision making, concepts and guidelines for working with party policies were consistent, beneficial for the nation and the people, and based upon the democratic system with the King as Head of State.